Challenges of internationalization via e-commerce : Case study of Finnish Sustainable Fashion SME expanding to Norway - Gashi, Dafina (My University, 2025)
This research aims to explore and analyze the key challenges faced by Finnish sustainable fashion SME when expanding to the Norwegian market through e-commerce. The thesis also focuses in understanding the internationalization motives of the company and explore their e-commerce as exporting channel to Norway. While existing academic literature extensively discusses internationalization and export challenges from various business and market perspectives, there is a lack of research specifically focusing on sustainable fashion SMEs expanding into the Norwegian market. The theoretical framework of the study examines the internationalization process through the Uppsala models and export barrier classifications, emphasizing experiential learning, market knowledge, and the role of digital platforms in international expansion. The theoretical framework was built from the perspective of SME’s that uses e-commerce business for cross- border activities. The key themes include introducing the internationalization concepts and pathways, then also introducing the exporting barriers from the lenses of e-commerce. The methodology of the study is qualitative, using a single-case study design. The empirical data were collected through semi-structured thematic interviews with top management from a Finnish sustainable fashion SME actively involved in cross-border e-commerce. The research approach uses secondary data regarding Norwegian market which later supports the analysis of the research. The findings identify several recurring challenges, including inadequate market research, complex customs regulations, product pricing difficulties, and limited internal expertise on Norwegian legal requirements. The results suggest that while e-commerce provides a cost- effective and scalable entry model for the Norwegian market, the lack of regulatory knowledge and resource constraints can hinder effective market penetration. The study offers practical insight for SMEs in similar industries and highlights the importance of supporting structures, such as logistics partnerships and external advisory services. Future research could examine multiple SME from within the sustainable industry or in a larger scale on the internationalization challenges in the Norwegian market. Another future research suggestion would be focusing on finding solutions or best practices on the challenges faced. Lastly, one future research proposal would be researching Internationalization readiness in relation to managerial capabilities.

Tämän tutkimuksen tavoitteena on tutkia keskeisiä haasteita, joita suomalainen kestävään muotiin keskittyvä pk-yritys kohtaa laajentuessaan Norjan markkinoille verkkokaupan avulla. Tutkielma keskittyy yrityksen kansainvälistymismotiivien ymmärtämiseen sekä verkkokaupan hyödyntämiseen vientikanavana Norjaan. Vaikka akateeminen kirjallisuus käsittelee laajasti kansainvälistymistä ja viennin haasteita eri liiketoiminta- ja markkinanäkökulmista, tutkimusta kestävän muodin pk-yritysten kansainvälistymisestä Norjan markkinoille on tehty vähän. Tutkimuksen teoreettinen viitekehys tarkastelee kansainvälistymisprosessia Uppsalan mallien ja vientiesteiden luokittelun kautta, painottaen kokemuksellista oppimista, markkinatuntemusta sekä digitaalisten alustojen roolia kansainvälistymisessä. Viitekehys on rakennettu pk-yritysten näkökulmasta, jotka käyttävät verkkokauppaa viennissä. Keskeisiä teemoja ovat kansainvälistymisen käsitteet ja etenemismallit sekä vientiesteet verkkokaupan näkökulmasta. Tutkimusmenetelmä on laadullinen ja perustuu yhden tapaustutkimuksen analyysiin. Empiirinen aineisto kerättiin puolistrukturoiduilla teemahaastatteluilla suomalaisen kestävän muodin pk-yrityksen johdosta, joka toimii aktiivisesti kansainvälisessä verkkokaupassa. Tutkimuksessa hyödynnetään myös sekundääristä aineistoa Norjan markkinasta, joka tukee tutkimuksen analyysipuolta. Tutkimustuloksissa tunnistetaan useita toistuvia haasteita, kuten puutteellista markkinatutkimusta, monimutkaisia tullimääräyksiä, yrityksen hinnoitteluhaasteita sekä rajallista asiantuntemusta Norjan lainsäädäntöön liittyen. Tulokset osoittavat, että vaikka verkkokauppa tarjoaa kustannustehokkaan ja skaalautuvan markkinoille vientimallin Norjaan, sääntelytiedon puute ja rajalliset resurssit voivat estää tehokkaan markkinoille pääsyn. Tutkimus tarjoaa käytännönläheisiä oivalluksia vastaaville pk-yrityksille ja korostaa verkostorakenteiden, kuten logistiikkakumppanuuksien ja ulkoisten neuvontapalveluiden merkitystä. Tulevaisuuden tutkimuksissa voitaisiin tarkastella useampia kestävän muotialan pk-yrityksiä tai laajemmassa mittakaavassa kansainvälistymisen haasteita Norjan markkinoilla. Toinen tutkimusehdotus voisi keskittyä ratkaisujen tai parhaiden käytäntöjen löytämiseen tunnistettuihin haasteisiin. Kolmantena tutkimusaiheena voitaisiin tarkastella kansainvälistymisvalmiutta johtajuusosaamisen näkökulmasta.
Keywords: small and medium-sized enterprises; internationalisation; electronic commerce; Norway; marketing; international market; export; clothing industry; international trade; marketing research; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business